(Survivig) living on the streets in times of the Covid-19 pandemic - Xavier, Bárbara Letícia de Queiroz; Oliveira, Vinícius Rodrigues de; Teixeira, Brenda dos Santos; Soares, Amanda; Amaral, Jeferson Falcão do; Menezes, Harlon França de; Silva, Richardson Augusto Rosendo da (Revista de Enfermagem da UFPI, 2024)
Objective: To understand the repercussions and ways of coping with Covid-19 in the daily lives of the homeless population. Method: Qualitative study, carried out in a capital of the Northeast of Brazil, from May to July 2021. Thirty-one people who are part of the homeless population participated through an interview. Data processing took place using the IRaMuTeQ 0.7 alpha 2 software, resulting in analyses: similarity, word cloud and dendrogram. Thematic analysis was used, according to Bardin. Results: From the discourse of the homeless population with Covid-19, it was observed in relation to health care: provision of aid in the pandemic period; fear of becoming ill by Covid-19 and acquisition of barrier measures; needs faced during the pandemic and implementation of hygiene measures. Living on the streets increased its vulnerability during the pandemic period, although in our study it was observed that health care gained potential through the availability of the office on the street, with its humanization of assistance and welcoming care. Conclusion: The impacts of Covid-19 on the ways of coping with HLP occurred in socio-emotional aspects, in the provision of prevention measures and social support.